Edugames Baamboozle: Increasing Interest in Learning Fine Arts for Students Kelas XI in SMA Negeri 4 Sidrap Through Game-Based Learning - Ulfianti, Ulfianti; Syamsunir, Syamsunir; Nurmayanti, Nurmayanti (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
The purpose of this study is to ascertain how effective Edugames Baamboozle in increasing interest in learning Fine Arts students in SMA Negeri 4’s class XI Sidrap. With a pretest- posttest control group design, this study employs a proper experimental research design. Class XI IPA 1, which had 28 students as the control group, and class XI IPA 2, which had 26 students as the experimental group, comprised the study’s sample. From the findings of this investigation that have been analyzedthe control class’s average value was 68.89% in the experimental class 83.83%. The N-Gain test findings in the control class were 27.35%, while 61.56% in the experimental class. In light of these findings, it may be said that the use of edugames Baamboozle is effective in increasing interest in learning Fine Arts of SMA Negeri 4 Sidrap class XI students. Key Words: Learning, Baamboozle Edugames, Learning Interest.